Are childhood factors predictive of adult health literacy? A longitudinal birth cohort analysis - I. Solis-Trapala; P. Campbell; R.J. Lacey; G. Rowlands; K.M. Dunn; J. Protheroe (Elsevier, 2023)
Health literacy (HL), defined as the ability of an individual to understand and appraise health information to make informed decisions on their health, helps maintain and improve one's health and thus reduce the use of healthcare services. There is a recognised global effort to address insufficient HL in early life and understand how HL develops. This study examined the association of a range of factors including educational, speech and language ability, health and healthcare engagement, sleep problems, mental health, demographic, environmental, and maternal factors at different childhood stages (from 5 years to 11 years) with later adult HL at age 25. HL was measured using a HL ordinal score (insufficient, limited, or sufficient) derived from the European Literacy Survey Questionnaire-short version (HLS-EU-Q16) within a large UK based birth cohort (Avon Longitudinal Study of Parents and Children: ALSPAC study). Univariate proportional odds logistic regression models for the probability of having higher levels of HL were developed.Results of analysis of 4248 participants showed that poorer speech and language ability (aged 9 years, OR 0.18 95% CI 0.04 to 0.78), internalising in child (age 11 years, OR 0.62 95% CI 0.5 to 0.78), child depression (age 9 years, OR 0.67 95% CI 0.52 to 0.86), and the presence of maternal depression (child age 5, OR 0.80 95% CI 0.66 to 0.96), reduced the odds of sufficient HL when adult. Our results suggest some useful markers to identify children at potential risk of low HL that could be targeted for research into future interventions within school settings, for example, child's speech and language capability. In addition, this study identified child and maternal mental health as factors associated with later development of limited HL and future research should consider what potential mechanisms might explain this link.